Encrypted control of networked cyber-physical systems - Zhang, Jingze (Nanyang Technological University, 2024)
Renewable energy sources have been widely used in recent years. While supplementing the power system with energy, it also introduces higher fluctuation, which places higher requirements on the robustness of power system operation. Economic dispatch (ED) is about the operation of microgrids and provides a guarantee for the stable and cheap and environmentally friendly operation of power systems. Hence, it’s very necessary to introduce encrypted control in the ED process. This dissertation focuses on encrypted control of networked cyber-physical systems, including microgrids. This dissertation includes following works: 1. This dissertation focuses on consensus-based distributed algorithms. To facilitate data encryption, a recently proposed new dynamic quantization algorithm similar to the estimator is introduced, and other quantization algorithms are introduced for comparison. 2. A new modern programming languages-based quantization algorithm is proposed, and the properties of the homomorphic encryption algorithm Paillier are used to ensure that the information transmitted over the network is protected from external malicious attacks, while ensuring that the private information of each node is not disclosed. 3. The CKKS encryption algorithm is introduced to further improve the operating speed of the encrypted control scheme in ED and reduce bandwidth usage. Finally, based on the above, this dissertation illustrates the capabilities of the presented solution in terms of privacy protection by comparing simulation cases, and compares it with existing encrypted control solutions.